Sistem Informasi Akreditasi Program Studi di Fakultas Ilmu Komputer dan Teknologi Informasi Universitas Mulawarman - Putut Pamilih Widagdo; Ramadiani Ramadiani; Septya Maharani; Eko Junirianto (Program Studi Sistem Informasi, 2019)
The study program is organized based on the curriculum so that students capable the knowledge, attitudes, and behavior accordingly. Accreditation is a comprehensive process of evaluation and assessment of commitment to the quality and capacity of implementing a tertiary Tridarma program, to determine the feasibility of a study program to hold its academic program. Decisions regarding quality are based on evaluation and assessment of various evidence with the standards set by Accreditation from National Accreditation Board for Higher Education (BAN-PT). Accreditation is a reflection of the totality of conditions and input characteristics, processes, outputs, results, and impacts, or performance. Study Program Accreditation Information System of Mulawarman University's Faculty of Computer and Information Technology (FKTI) is an application that is used to facilitate assessment based on BAN-PT forms standards and effort to readily implement study program accreditation to improve the quality value of accreditation. This research developed information system accreditation study program that facilitates the assessment and preparation of data internally as well as being able to store, distribute and adjust evidence according to quality standards BAN-PT forms instruments. With existence of an accreditation information system, it is expected to increase productivity, effectiveness and efficiency to achieve good quality accreditation numbers. Keywords: information system, accreditation, study program, quality, BAN-PT